Exploring the Author–Translator–Publisher Relationship Using Bourdieu's Capital: A Case Study of Jin Yong's Martial Arts Fiction. - Sun, Yingbin; Liang, Linxin (Critical Arts: A South-North Journal of Cultural & Media Studies, 2023)
Jin Yong was a successful martial arts fiction writer in China who had 15 prestigious works published. He created a fantasy world of wuxia for numerous Sinophone and non-Sinophone readers. Despite cultural and linguistic differences, four of Jin Yong's works were translated into English. In the translation and international circulation of Jin Yong's work, the contributions of the author, translators, and publishers—the three major cultural active agents in the transnational literary field—should be noted. By referencing Bourdieu's concept of capital, this study utilizes descriptive and explanatory methods to identify the author–translator–publisher relationship and observe how these agents interact by leveraging their capital, so as to improve the international recognition of Jin Yong's works.